EVALUASI KRIM TABIR SURYA KOMBINASI EKSTRAK BONGGOL PISANG KEPOK DAN DAUN KELOR - andini; Rahmawati, Gia; Damayanti, Alvira; Wulandari, Ayu Wanda Yuli; Evan, Muhammad (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
The utilization of natural materials as active ingredients in cosmetic formulations combining two natural substances is rarely encountered. It is essential to conduct an evaluation of the combination cream derived from natural materials, both chemically and physically. This research aimed to evaluate the active ingredient content that could be processed as sunscreen and to assess the physical quality of the cream. The methods employed included extract preparation, cream formulation, physical quality evaluation, antioxidant testing, and SPF testing. The results of the physical quality tests indicate that the M/A cream meets the required physical quality standards. The antioxidant test results show that FI has moderate activity, FII has strong activity, and FIII has very strong activity, while the SPF test results for FI, FII, and FIII indicate maximum protection. The conclusion of this research is that the evaluation of the physical quality of the cream meets the established criteria, the antioxidant test demonstrates strong activity, and the SPF test indicates maximum protection.